Komparasi Tingkat Ansietas Santri Putri Penghafal Al-Qur’an Program Takhassus dan Program Biasa - Mardiyan Hayati; Rochman Basuki; Aurora Janatul Makwa (CV. ITTC INDONESIA, 2026)
The aim of this research is to find out the comparison of the anxiety levels of high school students who take part in the Takhassus program with the regular program. This research method uses an analytical observational research type with a cross sectional design. The sample in this study was female students from class XII of the Tahfidh Al-Amien Prenduan Islamic Boarding School who met the inclusion and exclusion criteria. The sampling technique was carried out using a stratified random sampling technique. Data taken included the program followed, namely takhassus or usual, the number of juz that had been memorized and the Depression Anxiety Stress Scale 42 questionnaire. Data analysis for hypothesis testing used the Mann Whitney test. The results of this research have a p value of 0.020 (≤0.05), which means that the level of anxiety of students in the Takhassus program is lower than the level of anxiety of students who take part in the regular program.